ANALISIS REGRESI LINEAR BERGANDA PADA HUBUNGAN ANTARA TINGGI BADAN, BERAT BADAN DAN USIA TERHADAP PERKEMBANGAN POTENSI AKADEMIK ANAK USIA DINI (STUDI KASUS: RA - ADDURIYAT) - Handayani, Putri (Jurnal Riset Informatika dan Teknologi Informasi, 2024)
To support the development of academic potential of RA Adduriyat students, an in-depth understanding of the components that influence the development of academic potential in children is needed. This study will use multiple linear regression focusing on three factors that influence academic potential, namely: weight, height, and age. The population in this study is all students of RA Adduriyat. Data in the form of secondary data obtained from one of the educators at RA Adduriyat. The data obtained in this study were analyzed descriptively and then analyzed using multiple linear regression tests which aim to make predictions of the value of a dependent variable based on the value of the independent variable. The tools used in this research are orange software.